2020
DOI: 10.1016/j.psj.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of individual broilers to variation in amino acid digestibility in soybean meal and the efficacy of an exogenous monocomponent protease

Abstract: A total of 72 male Ross 308 broilers were reared to day 34 on a standard wheat and soy-based diet and then offered one of the four semisynthetic experimental diets, comprising two different soybean meal sources either without or with exogenous protease (treatments therefore offered in a 2*2 factorial arrangement). Each experimental diet was fed to 18 individually housed birds from 34 to 37 D after which ileal digesta were collected and digestibility coefficients were calculated. The two soybean meal sources we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(19 reference statements)
0
2
0
2
Order By: Relevance
“…In the current study, lysine content in the SBM was 5.62 g/100 g CP, which can be considered as low and closely resembles the lower values reported by Ibáñez et al [ 24 ] and Ravindran et al [ 25 ] in meals from different countries of origin, which could be related to harsh processing conditions during the production of the meal. Recent studies performed in Australia [ 26 ], reported SBM with lysine contents averaging 4.82 g/100 g CP. Similar contents can only be found in the SBM that was autoclaved for 60 min in the present study (4.70 g/100 g CP).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, lysine content in the SBM was 5.62 g/100 g CP, which can be considered as low and closely resembles the lower values reported by Ibáñez et al [ 24 ] and Ravindran et al [ 25 ] in meals from different countries of origin, which could be related to harsh processing conditions during the production of the meal. Recent studies performed in Australia [ 26 ], reported SBM with lysine contents averaging 4.82 g/100 g CP. Similar contents can only be found in the SBM that was autoclaved for 60 min in the present study (4.70 g/100 g CP).…”
Section: Discussionmentioning
confidence: 99%
“…Animals with a lower digestive capacity, more sensitivity to dietary antinutrients, poor disease or general health status or with compromised immune or microbiome function or exposed to environmental or other stressors will typically deliver below average digestibility values and may, in turn, benefit more from exogenous feed enzymes. For example, Cowieson et al. (2020) noted that a single soybean meal fed to 18 individually housed broilers returned a standardised amino acid digestibility ranging from 54% to 80%.…”
Section: Interaction Between Dietary Fibre and The Enteric Microbiomementioning
confidence: 99%
“…Это подтверждается недавним изучением индивидуальной переваримости протеина соевого шрота из двух источников петушками Росс 308. Во время эксперимента источник соевого шрота и включение в рацион протеазы не оказывали влияния на потребление корма -это даёт основание считать, что наблюдаемые нижеуказанные различия были обусловлены изучаемыми факторами (Cowieson et al, 2020). В ряде исследований установлено, что под действием добавляемых протеаз повышение переваренных аминокислот происходит не пропорционально их составу в исходном рационе, сбалансированному с потребностями организма (Cowieson and Roos, 2014), что ведёт к отклонениям в формуле «идеального» аминокислотного состава протеина.…”
Section: действие протеазunclassified